Copy number variation analysis in Chinese children with complete atrioventricular canal and single ventricle - Xingyu Zhang; Bo Wang; Guoling You; Ying Xiang; Qihua Fu; Yongguo Yu; Xiaoqing Zhang (BMC, 2021)
Abstract Background Congenital heart disease (CHD) is one of the most common birth defects. Copy number variations (CNVs) have been proved to be important genetic factors that contribute to CHD. Here we screened genome-wide CNVs in Chinese children with complete atrioventricular canal (CAVC) and single ventricle (SV), since there were scarce researches dedicated to these two types of CHD. Methods We screened CNVs in 262 sporadic CAVC cases and 259 sporadic SV cases respectively, using a customized SNP array. The detected CNVs were annotated and filtered using available databases. Results Among 262 CAVC patients, we identified 6 potentially-causative CNVs in 43 individuals (16.41%, 43/262), including 2 syndrome-related CNVs (7q11.23 and 8q24.3 deletion). Surprisingly, 90.70% CAVC patients with detected CNVs (39/43) were found to carry duplications of 21q11.2-21q22.3, which were recognized as trisomy 21 (Down syndrome, DS). In CAVC with DS patients, the female to male ratio was 1.6:1.0 (24:15), and the rate of pulmonary hypertension (PH) was 41.03% (16/39). Additionally, 6 potentially-causative CNVs were identified in the SV patients (2.32%, 6/259), and none of them was trisomy 21. Most CNVs identified in our cohort were classified as rare (< 1%), occurring just once among CAVC or SV individuals except the 21q11.2-21q22.3 duplication (14.89%) in CAVC cohort. Conclusions Our study identified 12 potentially-causative CNVs in 262 CAVC and 259 SV patients, representing the largest cohort of these two CHD types in Chinese population. The results provided strong correlation between CAVC and DS, which also showed sex difference and high incidence of PH. The presence of potentially-causative CNVs suggests the etiology of complex CHD is incredibly diverse, and CHD candidate genes remain to be discovered.